Social housing, wellbeing and welfare - Gregory, James (Research fellow) (Policy Press, 2022)
The growing demand for social housing is one of the most pressing public issues in the UK today, and this book analyses its role and impact. Anchored in a discussion of different approaches to the meaning and measurement of wellbeing, the author explores how these perspectives influence our views of the meaning, value and purpose of social housing in today's welfare state. The closing arguments of the book suggest a more universalist approach to social housing, designed to meet the common needs of a wide range of households, with diverse socioeconomic characteristics, but all sharing the same equality of social status.The growing demand for social housing is one of the most pressing public issues in the UK today, and this book analyses its role and impact. Anchored in a discussion of different approaches to the meaning and measurement of wellbeing, the author explores how these perspectives influence our views of the meaning, value and purpose of social housing in today's welfare state. The closing arguments of the book suggest a more universalist approach to social housing, designed to meet the common needs of a wide range of households, with diverse socioeconomic characteristics, but all sharing the same equality of social status.--